Bacteria evoke alarm behaviour in zebrafish - Joanne Shu Ming Chia (Nature Portfolio, 2019)
When injured, fish release an alarm substance produced by club cells in the skin that elicits fear in members of their shoal. Here, the authors show that mucus and bacteria are transported from the external surface into club cells, and bacterial components elicit alarm behaviour, acting in concert with a substance from fish.